2000
DOI: 10.1177/014556130007900815
|View full text |Cite
|
Sign up to set email alerts
|

Otomycosis: A Clinicomycologic Study

Abstract: Otomycosis is a common fungal infection of the ear that is seen in the tropical and subtropical regions of the world. We performed mycologic analyses on debris and scraping samples from the external ear canals of 95 patients who had been clinically diagnosed with otomycosis. Seventy-one samples (74.7%) were positiveforfungal growth; two ofthese samples contained two fungi, bringing the total number ofisolates to 73. The most common pathogens were Aspergillus fumigatus (41.1% of all isolates), A niger (36.9 %),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
103
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 7 publications
19
103
4
2
Order By: Relevance
“…However it is more prevalent in hot, humid and dusty areas of the tropical and subtropical regions. This could be due to the high degree of humidity, hot weather and presence of dust in the environment, these features favouring the dissemination and growth of molds [7][8][9][10]21]. Pruritus was the most common symptom found in the otomycosis patients followed by otalgia, hearing loss and ear fullness, confirming the findings of earlier workers [8,10,22].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However it is more prevalent in hot, humid and dusty areas of the tropical and subtropical regions. This could be due to the high degree of humidity, hot weather and presence of dust in the environment, these features favouring the dissemination and growth of molds [7][8][9][10]21]. Pruritus was the most common symptom found in the otomycosis patients followed by otalgia, hearing loss and ear fullness, confirming the findings of earlier workers [8,10,22].…”
Section: Discussionsupporting
confidence: 76%
“…In our study we found 16% of the otomycosis patients had itching on other parts of body. A higher incidence of 35-50% of dermal fungal coinfection has been reported by other workers [7,28]. Dermatomycosis has been reported as one of the predisposing factor of otomycosis, which may be due to the autoinoculation of the dermatophytes from the infected parts of the body into the ear.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…While some studies have reported otomycosis to be more common among young men [1, 5, 7, 8, 15] as in our series, many others have reported it to be so among young females [2, 3, 14, 16, 17]. In our series the male : female ratio was 1.7 : 1.…”
Section: Discussioncontrasting
confidence: 59%